DEPICTING PERTINENT CURRICULUM HICCUPS CONSTRAINING STUDENTS PURSUING SENIOR NATIONAL CERTIFICATE - Tinyiko Josephine Nkuzana; Shuti Steph Khumalo (Social Sciences and Education Research Review)
The primary objective of schooling is to ensure that all learners succeed and complete their grades. This goal can only be achieved when all the role players are prepared, and all the conditions and opportunities are created for teaching and learning to take place. Despite these conditions, there are challenges which contribute towards poor leaner performance. The objective of this paper was to identify and characterize the pertinent factors which contribute to poor grade 12 learner performance in Limpopo Province, South Africa. In investigating this phenomenon, the researchers deployed interpretative research paradigm. Semi-structured interviews were administered to six secondary school principals to gain rich data. Findings demonstrate there are several varied pertinent challenges which account to poor grade 2 learner performance in Vhembe Education District, Limpopo, including absenteeism and health related matters, inadequate advocating learners code of conduct, poor socio-economic conditions, and volatility of the schooling environment due to school violence and gangsterism. This study is of great significance as it strengthens epistemic understanding on learner performance in secondary schools.